Applicability and Advantages of Flow artifact–insensitive Fluid-attenuated Inversion-recovery MR Sequences for Imaging the Posterior Fossa - Tanaka, Norimitsu; Abe, Toshi; Kojima, Kazuyuki; Nishimura, Hiroshi; Hayabuchi, Naofumi (American Journal of Neuroradiology, 2000)
Summary: We describe a new sequence, flow artifact–insensitive fluid-attenuated inversion recovery (FAIS-FLAIR), that capitalizes on the advantages of fluid-attenuated inversion recovery (FLAIR) while minimizing FLAIR-related artifacts such as those often encountered in the posterior fossa. Twenty-eight patients with posterior fossa disease underwent FAIS-FLAIR, conventional FLAIR, and spin-echo MR studies, and the findings yielded by the three techniques were compared. In this patient population, postcontrast FAIS-FLAIR imaging was obtained in 20 patients and compared with postcontrast T1-weighted images. The images were assessed for lesion conspicuity by three radiologists. FAIS-FLAIR markedly reduces the inflow artifacts from noninverted CSF on FLAIR images. It does so with and without contrast agent administration, and produces higher lesion conspicuity compared with T1- and T2-weighted spin-echo sequences and conventional FLAIR images of the posterior fossa.